First person – Suzie Buono and Arnaud Monseur (Disease Models & Mechanisms, 2022)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Suzie Buono and Arnaud Monseur are co-first authors on ‘ Natural history study and statistical modeling of disease progression in a preclinical model of myotubular myopathy’, published in DMM. Suzie is a senior associate scientist in the lab of Belinda Cowling at Dynacure, Illkirch, France, investigating rare diseases, especially centronuclear myopathies. Arnaud is a senior manager of statistics and data science at Pharmalex, Mont-St-Guibert, Belgium, working on innovative clinical trials, disease modelling and Bayesian statistics.